Changes in student entry competencies 2001–2017. Issue 7 (1st June 2022) - Hodds, Mark; Shao, Jia; Lawson, Duncan
ABSTRACT: Diagnostic testing on entry to university provides an opportunity for students to ascertain individual strengths and weaknesses and allows course teams to gain insight into the competencies of the whole cohort. Coventry University has been using the same diagnostic test since 1991 and a previous analysis showed students coming to Coventry University in 2001 were performing considerably worse than their counterparts in 1991. Given the changes to A level Mathematics that have taken place since 2001 and the recently implemented reforms to A level Mathematics in the UK, it is timely to review performance in the diagnostic test and to create a benchmark before students enter higher education with the new (linear) A levels. This paper therefore reports on the changing entry competencies of students at Coventry University from 2001 to 2017 and shows that there has been a general improvement in performance across all entry grades. However, students are still not performing at the same level as they were in 1991 and the gap between students with higher entry grades (A level A*–C) and lower entry grades (A level D–E) is getting wider.